River God Propaganda in a Septimius Severus Statue from Perge - Ahmet ÇELİK (Phaselis: Disiplinlerarası Akdeniz Araştırmaları Dergisi)
Lucius Septimius Severus was the Roman emperor from 193 to 211 AD. His portraits have an important place in the propaganda activities of Septimius Severus. It is evident that the initial portrait type may have served to propagandise the notion of the subject’s strength and agility as a soldier. The subsequent portrait may have been used to promote the subject’s affiliation with the House of Antonines. The third portrait, on the other hand, may have been employed to suggest that the subject was the deity Serapis or an individual bearing a similar resemblance. Finally, the final portrait may have been utilised to convey the image of a more mature and experienced statesman. It is also known that Septimius Severus propagandised Hercules (Heracles). However, the armoured statue portrait found in the F2 Fountain (Nymphaeum) of Perge in 1968 may indicate that he was making a new kind of propaganda. Because here the emperor has a very different beard structure. His beard is divided into sections with a deep drill. This beard, which is quite dissolved and compartmentalised, essentially resembles the beard of river gods. With this armoured statue, which basically shows ‘Adoption’ type hair and facial features, both Adoptive and the emperor must have been propagandised as a strong soldier. However, with this extremely unique beard in the statue belonging to Fountain F2, Septimius Severus resembles a river god, and therefore, it may have been propagandised that he was a river god who brought water to the city or someone who resembled a river god.